Anticonvulsant effects of aqueous and ethanolic extracts of Hypericum perforatum L. in mice - H Hosseinzadeh; GR Karimi; M Rakhshanizadeh (Institue of Medicinal Plants, ACECR, 2004)
We studied the anticonvulsant activity of the aqueous and ethanolic extracts of Hypericum perforatum aerial parts in mice. The pentylenetetrazole (PTZ) and the maximal electroshock seizure (MES) tests were used for assessing the anticonvulsive effects of this plant. In the PTZ test, the extracts (0.1-1 g/kg, i.p.) delayed the onset of tonic convulsions and protected mice against mortality. In the MES test, both extracts did not show antiseizure activity. L-NAME (1-10 mg/kg, i.p.), a nitric oxide (NO) synthase inhibitor, reduced the anticonvulsant activity of the extracts. The results of this study indicate that the extracts of H. perforatum aerial parts could contribute to the control of petit mal seizure and this effect may be partially mediated by nitric oxide pathway.